COVID-19: The world on pause. How we face this new pandemic? - Lapman, Gabriel (2020)
The Covid-19 pandemic, popularly known as coronavirus, was announced in an article by the American Society of Microbiology that already in 2007 warned about the dangers of the consumption of exotic animals in different Chinese communities. The background of SARS and MERS helps us understand that humanity is not prepared for such severe contingencies. Economies are sold out and there is no leadership; health systems are deficient: the result of years of underinvestment, low salaries and lack of qualified personnel to attend, follow, control and direct infectious diseases.